Molecular T2 asthma phenotypes are stable but heterogeneous: the usefulness of periostin for endotyping - Bobolea, Irina; Guillén-Vera, Daniela; De las Cuevas-Moreno, Natividad; García-Granero, Diego Blanco; Loli-Ausejo, David; Melero-Moreno, Carlos (Frontiers in Allergy, 2023)
is responsible for the conception and design of the study, coordination and supervision of the study, recruitment and follow-up of patients, analysis and interpretation of data, drafting the manuscript, critical revision for important intellectual content and approval of the final draft. D. Guillén contributed to the collection of data, analysis and interpretation of data, drafting the manuscript, critical revision for important intellectual content and approval of the final draft. N. de las Cuevas performed the periostin measurements, contributed to the analysis and interpretation of data and approval of the final draft. D. Blanco contributed to the acquisition of data, critical review for important intellectual content and approval of the final draft. D. Loli-Ausejo contributed to the critical revision of the manuscript for intellectual content and approved of the final draft.C. Melero Moreno contributed to the analysis and interpretation of data, supervised the study, critically revised the manuscript and approval of the final draft.